Mini Grids in Kenya : A Case Study of a Market at a Turning Point - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2017)
The Global Facility on Mini Grids of the Energy Sector Management Assistance Program (ESMAP) hired Castalia to study the regulation of mini grids in six jurisdictions in Sub-Saharan Africa and Asia (Kenya, Tanzania, and Nigeria; and Bangladesh, Cambodia, and the state of Uttar Pradesh in India). The study’s objective is to understand what regulatory settings governments may adopt to scale up electrification through private development of mini grids, drawing on the experience of these six jurisdictions; provide technical assistance to four countries that want to further develop their mini grids framework; and disseminate findings and recommendations globally to inform successful mini grids regulation. The study focuses on mini grids defined as small, privately-owned and operated systems with generation of up to 10 megawatts (MW) capacity and a network that distributes power to several customers. The study includes small mini grids of less than 1 kilowatt (kW) capacity, also known as ‘micro’ or ‘pico’ grids. The six case studies are intended to be combined in one report. The report is to provide a cross-country comparison of these topics: it examines side by side how each of the countries studied have responded to a specific regulatory question, and presents a decision-tree approach to developing regulatory frameworks for mini grids. This case study is based on in-depth interviews with a number of key stakeholders in Kenya, conducted during and after a research trip in September 2017. The supplemented the insights gained from these interviews with extensive background research. Several experts in the Kenya context and mini grids more broadly reviewed this case study for accuracy and clarity, and we have incorporated their comments while retaining a neutral fact-based position.